Nanoimprint resist underlayer film forming composition

A novolac resin-based resist underlayer film composition addresses adhesion and peeling issues in nanoimprint technologies by enhancing hydrophobicity and planarization, with adjustable optical constants and etching rates, improving process compatibility and reducing defects.

JP7601005B2Active Publication Date: 2024-12-17NISSAN CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021565526
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-12-10
Publication Date
2024-12-17
Estimated Expiration
2040-12-10

AI Technical Summary

Technical Problem

Existing nanoimprint technologies face issues with adhesion between the resist composition and the base material, leading to pattern peeling defects, and the need for a film that exhibits good planarization properties and high hydrophobicity while improving adhesion with hydrophobic upper layer films, with adjustable optical constants and etching rates.

Method used

A resist underlayer film composition containing a novolac resin with specific molecular structures, which includes aromatic rings and heterocycles, and optionally crosslinking agents, acids, and surfactants, to enhance hydrophobicity and adhesion, and adjust optical constants and etching rates.

Benefits of technology

The composition achieves high hydrophobicity and improved adhesion with hydrophobic upper layers, while providing good planarization and adjustable optical constants and etching rates, reducing pattern peeling defects and enhancing process compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601005000001
    Figure 0007601005000001
  • Figure 0007601005000002
    Figure 0007601005000002
  • Figure 0007601005000003
    Figure 0007601005000003
Patent Text Reader

Abstract

Provided is a composition for forming a resist underlayer film for nanoimprinting, said composition demonstrating good planarizability and particularly high hydrophobicity even during high-temperature firing, as well as being able to be adjusted, by changing the molecular framework thereof, to an optical constant or etching speed that is suitable for a process. This composition for forming a resist underlayer film for nanoimprinting includes a novolac resin that has a repeating unit structure represented by formula (1). [In formula (1), group A represents an organic group having an aromatic ring, a condensed aromatic ring, or a condensed aromatic heterocycle, group B represents an organic group having an aromatic ring or a condensed aromatic ring, group E represents a single bond or a branched or straight-chain C1-10 alkylene group that may be substituted and may include an ether bond and / or a carbonyl group, group D represents an organic group that has 1 to 15 carbon atoms and is represented by formula (2) (in which R1, R2, and R3 each independently represent a fluorine atom, or a straight-chain, branched-chain, or cyclic alkyl group, and any two of R1, R2, and R3 may be bonded to one another to form a ring), and n represents a number from 1 to 5.]
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resist underlayer film-forming composition for nanoimprints, a resist underlayer film that is a cured product of a coating film made of the composition, a method for producing the resist underlayer film, and a method for forming a pattern and a method for producing a semiconductor device that utilize the resist underlayer film. [Background technology]

[0002] In the manufacture of semiconductor devices and MEMS, which require miniaturization, photo-nanoimprint technology, which can form fine structures on the order of a few nanometers on a substrate, has attracted attention. This is a technology in which a curable composition (resist) is applied onto a substrate (wafer), a mold with a fine concave-convex pattern formed on its surface is pressed against it, the resist is cured in this state by heat or light, the concave-convex pattern of the mold is transferred to the cured resist film, and the mold is then removed to form a pattern on the substrate.

[0003] In a typical photo-nanoimprint technique, first, a liquid resist composition is dropped onto a pattern formation region on a substrate using an inkjet method or the like, and the droplets of the resist composition are spread onto the substrate (press-spread). Next, this resist composition is molded using a mold (mold) that is transparent to the irradiated light and has a pattern formed thereon. At this time, the droplets of the resist composition spread over the entire gap between the substrate and the mold by capillary action (spread). The resist composition also fills the inside of the recesses on the mold by capillary action (fill). The time required for the spreading and filling to be completed is the filling time. After the filling of the resist composition is completed, the resist composition is hardened by irradiating light, and then the two are separated. By carrying out these steps, a resist pattern having a predetermined shape is formed on the substrate.

[0004] In the mold release process of the photo-nanoimprint technique, the adhesion between the resist composition and the substrate is important. If the adhesion between the resist composition and the substrate is low, when the mold is released in the mold release process, a part of the photocured product obtained by curing the resist composition may peel off while still adhering to the mold, resulting in a pattern peeling defect. As a technique for improving the adhesion between the resist composition and the substrate, a technique for forming an adhesion layer between the resist composition and the substrate, which is a layer for adhering the resist composition to the substrate, has been proposed.

[0005] In addition, a highly etch-resistant layer may be used for pattern formation in nanoimprinting. Organic materials and silicone materials are generally used as materials for the highly etch-resistant layer. Furthermore, an adhesion layer or a silicone layer containing Si may be formed on the nanoimprint resist underlayer film by coating or deposition. When the adhesion layer or the silicone layer containing Si is hydrophobic and exhibits a high pure water contact angle, it is expected that the underlayer film is also hydrophobic and exhibits a high pure water contact angle, which increases adhesion between the films and makes them less likely to peel off.

[0006] Since it is known that He, H2, N2, air, etc. are relatively hydrophobic at room temperature, they have a high affinity with a membrane with a high contact angle, and it is expected that the gas permeability will increase. For this reason, it is preferable that the underlayer membrane material also has a high water contact angle. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-36725 A Summary of the Invention [Problem to be solved by the invention]

[0008] Therefore, the problem that the present invention aims to solve is to provide a resist underlayer film-forming composition for nanoimprints that exhibits good planarization properties, gives a film having high hydrophobicity upon baking, is capable of enhancing adhesion to a hydrophobic overlying film, and further allows the optical constants and etching rate to be adjusted to suit the process by modifying the molecular skeleton of the resin. [Means for solving the problem]

[0009] The present invention encompasses the following: [1] The following formula (1): [ka] [In formula (1), Group A represents an organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle; Group B represents an organic group having an aromatic ring or a condensed aromatic ring; The group E represents a single bond or an optionally substituted branched or linear alkylene group having 1 to 10 carbon atoms which may contain an ether bond and / or a carbonyl group, Group D is [ka] (In the formula, R 1 , R 2 , R 3 are each independently a fluorine atom or a linear, branched, or cyclic alkyl group; R 1 , R 2 , R 3 Any two of the above may be bonded to each other to form a ring. n represents a number from 1 to 5.] The novolak resin includes a repeating unit structure represented by A composition for forming a resist underlayer film for nanoimprinting. [2] The resist underlayer film forming composition for nanoimprints according to [1], wherein the group D is a tert-butyl group or a trifluoromethyl group. [3] The resist underlayer film forming composition for nanoimprints according to [1] or [2], wherein the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in Group A is an organic group having one or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or fused rings of a benzene ring and a heterocycle or an aliphatic ring. [4] The resist underlayer film forming composition for nanoimprints according to any one of [1] to [3], wherein the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in Group A is an organic group having 6 to 30 carbon atoms which may contain at least one heteroatom selected from N, S and O on, within, or between the rings.

[0010] [5] The resist underlayer film forming composition for imprints according to any one of [1] to [4], wherein the group A is at least one selected from the following: [ka] (In the formula, i, j, m, and n each independently represent 1 or 2. G represents a direct bond or any of the following formulae: [ka] L and M each independently represent a hydrogen atom, a phenyl group, or C 1-3 represents an alkyl group. [6] The resist underlayer film forming composition for nanoimprints according to any one of [1] to [5], wherein the group B is phenylene, biphenylene, naphthalenediyl, anthracenediyl, or phenanthrenediyl. [7] The resist underlayer film forming composition for nanoimprints according to any one of [1] to [6], wherein the group E is a single bond or a linear alkylene group having 1 to 6 carbon atoms. [8] The resist underlayer film forming composition for imprints according to any one of [1] to [7], wherein Group E is a single bond. [9] The resist underlayer film forming composition for nanoimprints according to any one of [1] to [8], which exhibits a contact angle with pure water of 76° or more when baked at 240°C, and exhibits a contact angle with pure water of 70° or more when baked at 350°C.

[10] The resist underlayer film forming composition for imprints according to any one of [1] to [9], further comprising a crosslinking agent.

[11] The nanoimprint resist underlayer film forming composition according to any one of [1] to

[10] , further comprising at least one selected from the group consisting of acids, salts thereof, and acid generators.

[12] The resist underlayer film forming composition for nanoimprints according to

[10] or

[11] , which exhibits a contact angle with pure water of 65° or more when baked at 350°C.

[0011]

[13] A resist underlayer film which is a cured product of a coating film comprising the resist underlayer film forming composition for nanoimprints according to any one of [1] to

[12] .

[14] A method for producing a resist underlayer film, comprising applying the resist underlayer film forming composition for nanoimprints according to any one of [1] to

[12] onto a semiconductor substrate, and baking the composition.

[15] A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of [1] to

[12] ; applying a curable composition onto the resist underlayer film; contacting the curable composition with a mold; A step of irradiating the curable composition with light or an electron beam to form a cured film; and A step of separating the cured film from the mold; A pattern forming method comprising the steps of:

[16] The step of applying a curable composition onto the resist underlayer film comprises: forming an adhesion layer and / or a silicone layer containing 99% by mass or less, or 50% by mass or less of Si, on the resist underlayer film by coating or vapor deposition, and applying a curable composition thereon; The pattern forming method according to

[15] ,

[17] A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of [1] to

[12] ; forming a resist film thereon; A step of forming a resist pattern by irradiation with light or an electron beam and development; Etching the underlayer film using the formed resist pattern; and A process for processing a semiconductor substrate using a patterned underlayer film A method for manufacturing a semiconductor device comprising the steps of:

[18] A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of [1] to

[12] ; forming a hard mask thereon; Further, a step of forming a resist film thereon; A step of forming a resist pattern by irradiation with light or an electron beam and development; Etching the hard mask using the formed resist pattern; Etching the underlayer film with a patterned hard mask; and A process for processing a semiconductor substrate using a patterned resist underlayer film. A method for manufacturing a semiconductor device comprising the steps of: Effect of the Invention

[0012] The novolac resin according to the present invention exhibits a specifically high pure water contact angle (= hydrophobicity) not only when baked at a low temperature but also when baked at a high temperature. In addition, the novolac resin according to the present invention exhibits a specifically high pure water contact angle (= hydrophobicity) when baked at a high temperature, even when mixed with a crosslinking agent, an acid catalyst, and a surfactant to form a material. This makes it possible to increase the adhesion with a hydrophobic upper layer film, and is also expected to exhibit good permeability to hydrophobic gases. Furthermore, the novolac resin according to the present invention exhibits good planarization properties, and by changing the molecular skeleton, the optical constants and etching speed can be adjusted to suit the process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Nanoimprint resist underlayer film forming composition] The nanoimprint resist underlayer film forming composition according to the present invention has the following formula (1): [ka] [In formula (1), Group A represents an organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle; Group B represents an organic group having an aromatic ring or a condensed aromatic ring; The group E represents a single bond or an optionally substituted branched or linear alkylene group having 1 to 10 carbon atoms which may contain an ether bond and / or a carbonyl group, Group D is [ka] (In the formula, R 1 , R 2 , R 3 are each independently a fluorine atom or a linear, branched, or cyclic alkyl group; R 1 , R 2 , R 3 Any two of the above may be bonded to each other to form a ring. n represents a number from 1 to 5.] The composition contains a novolac resin having a repeating unit structure represented by the formula: and optionally contains a solvent and other components. The following will explain each component in order.

[0014] [Novolac resin having a repeating unit structure represented by formula (1)] The "organic group having an aromatic ring" in the group A and group B refers to a group having a hydrocarbon that exhibits aromaticity in a single ring. For example, groups derived from benzene, cyclooctatetraene, toluene, xylene, mesitylene, cumene, and styrene having any substituent can be mentioned. In addition, organic groups having a condensed ring of an aromatic ring such as benzene with an aliphatic ring such as cyclohexane, cyclohexene, methylcyclohexane, and methylcyclohexene, and organic groups having a condensed ring of an aromatic ring such as benzene with a heterocycle such as furan, thiophene, pyrrole, imidazole, pyran, pyridine, pyrimidine, pyrazine, pyrrolidine, piperidine, piperazine, and morpholine are also included.

[0015] The "organic group having a fused aromatic ring" in Group A and Group B refers to a group having a hydrocarbon that exhibits aromaticity in a fused ring, such as a group derived from indene, naphthalene, azulene, anthracene, phenanthrene, naphthacene, triphenylene, pyrene, or chrysene.

[0016] The "organic group having a condensed aromatic heterocycle" in group A refers to a group that exhibits aromaticity in a condensed ring and has a hydrocarbon containing a heteroatom. Examples of such groups include groups derived from indole, purine, quinoline, isoquinoline, chromene, thianthrene, phenothiazine, phenoxazine, xanthene, acridine, phenazine, and carbazole. The aromatic ring, condensed aromatic ring, and condensed aromatic hetero ring may be linked to each other via an alkylene group or the like.

[0017] Preferably, the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in group A is an organic group having 6 to 30 carbon atoms. Preferably, the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in group A is an organic group having one or more benzene rings, naphthalene rings, or a fused ring of a benzene ring with a heterocycle or an aliphatic ring.

[0018] Preferably, the organic group having an aromatic ring, a condensed aromatic ring, or a condensed aromatic hetero ring in the group A is an organic group having 6 to 30 carbon atoms which may contain at least one heteroatom selected from N, S, and O on, in, or between rings. Examples of the heteroatom contained on the ring include a nitrogen atom contained in an amino group (e.g., a propargylamino group), a nitrogen atom contained in a cyano group, a formyl group, a hydroxyl group, a carboxyl group, an oxygen atom contained in an alkoxy group (e.g., a propargyloxy group), and a nitrogen atom and an oxygen atom contained in a nitro group. Examples of the heteroatom contained within the ring include an oxygen atom contained in a xanthene, and a nitrogen atom contained in a carbazole. Examples of the heteroatom contained between rings include a nitrogen atom, an oxygen atom, and a sulfur atom contained in a -NH- bond, a -NHCO- bond, a -O- bond, a -COO- bond, a -CO- bond, a -S- bond, a -SS- bond, and a -SO2- bond.

[0019] Preferably, the group A is at least one selected from the following: [ka] (In the formula, i, j, m, and n each independently represent 1 or 2. G represents a direct bond or any of the following formulae: [ka] L and M each independently represent a hydrogen atom, a phenyl group, or C 1-3 represents an alkyl group.

[0020] Preferably, the group A is at least one selected from the following: [ka]

[0021] Preferably, the group B is phenylene, biphenylene, naphthalenediyl, anthracenediyl, phenanthrenediyl.

[0022] The group D is an organic group having 1 to 15 carbon atoms represented by the above formula (2), preferably an organic group having 1 to 12 carbon atoms, 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 5 carbon atoms, or 1 to 4 carbon atoms.

[0023] R 1 , R 2 , R 3Examples of the "straight-chain, branched-chain, or cyclic alkyl group" in the above formula include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, a cyclopropyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, an n-pentyl group, a 1-methyl-n-butyl group, a 2-methyl-n-butyl group, a 3-methyl-n-butyl group, a 1,1-dimethyl-n-propyl group, a 1,2-dimethyl-n-propyl group, a 2,2-dimethyl-n-propyl group, a 1-ethyl-n-butyl group, a 2 ... n-Hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl cyclopropyl, 3-ethylcyclobutyl, 1,2-dimethylcyclobutyl, 1,3-dimethylcyclobutyl, 2,2-dimethylcyclobutyl, 2,3-dimethylcyclobutyl, 2,4-dimethylcyclobutyl, 3,3-dimethylcyclobutyl, 1-n-propylcyclopropyl, 2-n-propylcyclopropyl, 1-i-propylcyclopropyl, 2-i-propylcyclopropyl, 1,2,2-trimethylcyclopropyl, 1,2,3-trimethylcyclopropyl, 2,2,3-trimethyl-cyclopropyl, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl, and 2-ethyl-3-methyl-cyclopropyl groups. 1 , R 2 , R 3 Any two of these may be bonded to each other to form a ring. Preferably, the group D is a tert-butyl group or a trifluoromethyl group.

[0024] The group E is a single bond or a linear alkylene group having 1 to 6 carbon atoms. Examples of the linear alkylene group include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group. Preferably, the group E is a single bond.

[0025] n is a number from 1-5, 1-4, or 1-3, preferably 1, 2, 3, 4, or 5, more preferably 1, 2, 3, or 4, and most preferably 1, 2, or 3.

[0026] [Synthesis method] The novolak resin having the repeating unit structure represented by formula (1) can be prepared by a known method. For example, it can be prepared by condensing a ring-containing compound represented by HAH with an aldehyde compound represented by OHC-BED (wherein A, B, E, and D have the same meanings as above). The ring-containing compound and the aldehyde compound may be used alone or in combination of two or more. In this condensation reaction, the aldehyde compound can be used in a ratio of 0.1 to 10 moles, preferably 0.1 to 2 moles, per mole of the ring-containing compound.

[0027] Examples of the catalyst used in the condensation reaction include mineral acids such as sulfuric acid, phosphoric acid, and perchloric acid, organic sulfonic acids such as p-toluenesulfonic acid, p-toluenesulfonic acid monohydrate, and methanesulfonic acid, and carboxylic acids such as formic acid and oxalic acid. The amount of the catalyst used varies depending on the type of catalyst used, but is usually 0.001 to 10,000 parts by mass, preferably 0.01 to 1,000 parts by mass, and more preferably 0.05 to 100 parts by mass, per 100 parts by mass of the ring-containing compound (the total amount of the ring-containing compound when multiple types are used).

[0028] The condensation reaction can be carried out without a solvent, but is usually carried out using a solvent. The solvent is not particularly limited as long as it can dissolve the reaction substrate and does not inhibit the reaction. Examples of the solvent include 1,2-dimethoxyethane, diethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, tetrahydrofuran, and dioxane. The condensation reaction temperature is usually 40° C. to 200° C., preferably 100° C. to 180° C. The reaction time varies depending on the reaction temperature, but is usually 5 minutes to 50 hours, preferably 5 minutes to 24 hours.

[0029] The weight average molecular weight of the novolak resin having the repeating unit structure represented by formula (1) is usually 500 to 100,000, preferably 600 to 80,000, 800 to 60,000, or 1,000 to 50,000.

[0030] The novolak resin having a repeating unit structure represented by formula (1) according to the present invention is dissolved in a solvent and applied to a substrate (silicon wafer) without the addition of additives such as a crosslinking agent. When the resin is baked at 240°C, the resin exhibits a contact angle with pure water of 76° or more, and when the resin is baked at 350°C, the resin exhibits a contact angle with pure water of 70° or more.

[0031] [solvent] The resist underlayer film-forming composition for nanoimprinting according to the present invention may contain a solvent. The solvent is not particularly limited as long as it can dissolve the novolac resin having the repeating unit structure represented by formula (1) and any optional components added as necessary. In particular, since the resist underlayer film-forming composition for nanoimprinting according to the present invention is used in the form of a uniform solution, it is recommended to use a solvent generally used in lithography processes in combination with the composition in consideration of its coating performance.

[0032] Examples of such solvents include methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, methyl isobutyl carbinol, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoether ether acetate, propylene glycol monopropyl ether acetate, and propylene glycol monobutyl ether acetate. ethyl ether, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, methyl 2-hydroxy-3-methylbutanoate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl pyruvate, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol glycerol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monopropyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, propylene glycol dipropyl ether, propylene glycol dibutyl ether, ethyl lactate, propyl lactate, isopropyl lactate, butyl lactate, isobutyl lactate, methyl formate, ethyl formate, propyl formate, isopropyl formate, butyl formate, isobutyl formate, amyl formate, isoamyl formate, methyl acetate, ethyl acetate, amyl acetate, isoamyl acetate, hexyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, butyl propionate, isobutyl propionate, methyl butyrate,Ethyl butyrate, Propyl butyrate, Isopropyl butyrate, Butyl butyrate, Isobutyl butyrate, Ethyl hydroxyacetate, Ethyl 2-hydroxy-2-methylpropionate, Methyl 3-methoxy-2-methylpropionate, Methyl 2-hydroxy-3-methylbutyrate, Ethyl methoxyacetate, Ethoxyethylacetate, Methyl 3-methoxypropionate, Ethyl 3-ethoxypropionate, Ethyl 3-methoxypropionate, 3-Methoxybutyl acetate, 3-Methoxypropyl acetate, 3-Methyl-3-methoxybutyrate Examples of suitable solvents include butyl acetate, 3-methyl-3-methoxybutyl propionate, 3-methyl-3-methoxybutyl butyrate, methyl acetoacetate, toluene, xylene, methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, 2-heptanone, 3-heptanone, 4-heptanone, cyclohexanone, N,N-dimethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpyrrolidone, 4-methyl-2-pentanol, and γ-butyrolactone. These solvents can be used alone or in combination of two or more.

[0033] Among these, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate are more preferred, and propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate are even more preferred.

[0034] [Crosslinking agent] The nanoimprint resist underlayer film forming composition according to the present invention may contain a crosslinking agent. Examples of the crosslinking agent include melamine-based, substituted urea-based, and polymers thereof. The crosslinking agent preferably has at least two crosslink-forming substituents, and is a compound such as methoxymethylated glycoluril (e.g., tetramethoxymethylglycoluril), butoxymethylated glycoluril, methoxymethylated melamine, butoxymethylated melamine, methoxymethylated benzoguwanamine, butoxymethylated benzoguwanamine, methoxymethylated urea, butoxymethylated urea, or methoxymethylated thiourea. Condensates of these compounds may also be used.

[0035] In addition, a crosslinking agent having high heat resistance can be used as the crosslinking agent. As the crosslinking agent having high heat resistance, a compound containing a crosslinking-forming substituent having an aromatic ring (e.g., a benzene ring, a naphthalene ring) in the molecule can be preferably used.

[0036] The compound may be a compound having a partial structure of the following formula (4), or a polymer or oligomer having a repeating unit of the following formula (5). [ka] Above R 11 , R 12 , R 13 , and R 14 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and the above-mentioned examples of the alkyl group can be used. n1 is an integer of 1 to 4, n2 is an integer of 1 to (5-n1), and (n1+n2) is an integer of 2 to 5. n3 is an integer of 1 to 4, n4 is an integer of 0 to (4-n3), and (n3+n4) is an integer of 1 to 4. The number of repeating unit structures of the oligomers and polymers that can be used is in the range of 2 to 100 or 2 to 50.

[0037] Examples of the compounds, polymers and oligomers of formula (4) and formula (5) are shown below. [ka] [ka] [ka]

[0038] The above compounds are available as products of Asahi Yukizai Kogyo Co., Ltd. and Honshu Chemical Industry Co., Ltd. For example, among the above crosslinking agents, the compound of formula (4-23) is available from Honshu Chemical Industry Co., Ltd. under the trade name TMOM-BP, the compound of formula (4-24) is available from Asahi Yukizai Kogyo Co., Ltd. under the trade name TM-BIP-A, and the compound of formula (4-28) is available under the trade name PGME-BIP-A. The amount of the crosslinking agent added varies depending on the coating solvent used, the substrate used, the required solution viscosity, the required film shape, etc., but is 0.001% by mass or more, 0.01% by mass or more, 0.05% by mass or more, 0.5% by mass or more, or 1.0% by mass or more, and 80% by mass or less, 50% by mass or less, 40% by mass or less, 20% by mass or less, or 10% by mass or less, based on the total solid content. These crosslinking agents may cause a crosslinking reaction by self-condensation, but when crosslinkable substituents are present in the above-mentioned polymer of the present invention, they can cause a crosslinking reaction with the crosslinkable substituents.

[0039] [Acid and / or its salt and / or acid generator] The nanoimprint resist underlayer film forming composition according to the present invention can contain an acid and / or a salt thereof and / or an acid generator.

[0040] Examples of the acid include p-toluenesulfonic acid, trifluoromethanesulfonic acid, salicylic acid, 5-sulfosalicylic acid, 4-phenolsulfonic acid, camphorsulfonic acid, 4-chlorobenzenesulfonic acid, benzenedisulfonic acid, 1-naphthalenesulfonic acid, citric acid, benzoic acid, hydroxybenzoic acid, and naphthalenecarboxylic acid. As the salt, a salt of the above-mentioned acid can be used. Although the salt is not limited, ammonia derivative salts such as trimethylamine salts and triethylamine salts, pyridine derivative salts, morpholine derivative salts, etc. can be suitably used. The acid and / or its salt may be used alone or in combination of two or more kinds. The amount of the acid and / or its salt is usually 0.0001 to 20% by mass, preferably 0.0005 to 10% by mass, and more preferably 0.01 to 5% by mass, based on the total solid content.

[0041] The acid generator includes a thermal acid generator and a photoacid generator. Examples of thermal acid generators include 2,4,4,6-tetrabromocyclohexadienone, benzoin tosylate, 2-nitrobenzyl tosylate, K-PURE (registered trademark) CXC-1612, CXC-1614, TAG-2172, TAG-2179, TAG-2678, TAG2689, and TAG2700 (manufactured by King Industries), as well as SI-45, SI-60, SI-80, SI-100, SI-110, and SI-150 (manufactured by Sanshin Chemical Industry Co., Ltd.), and other organic sulfonic acid alkyl esters.

[0042] Photoacid generators generate acid when the resist is exposed to light. This allows the acidity of the underlayer to be adjusted. This is one way to match the acidity of the underlayer to that of the upper resist. Adjusting the acidity of the underlayer also allows the pattern shape of the resist formed in the upper layer to be adjusted. Examples of the photoacid generator contained in the resist underlayer film forming composition for nanoimprint of the present invention include an onium salt compound, a sulfonimide compound, and a disulfonyldiazomethane compound.

[0043] Examples of the onium salt compound include iodonium salt compounds such as diphenyliodonium hexafluorophosphate, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium nonafluoronormal butanesulfonate, diphenyliodonium perfluoronormal octanesulfonate, diphenyliodonium camphorsulfonate, bis(4-tert-butylphenyl)iodonium camphorsulfonate, and bis(4-tert-butylphenyl)iodonium trifluoromethanesulfonate, and sulfonium salt compounds such as triphenylsulfonium hexafluoroantimonate, triphenylsulfonium nonafluoronormal butanesulfonate, triphenylsulfonium camphorsulfonate, and triphenylsulfonium trifluoromethanesulfonate.

[0044] Examples of the sulfonimide compound include N-(trifluoromethanesulfonyloxy)succinimide, N-(nonafluoronormalbutanesulfonyloxy)succinimide, N-(camphorsulfonyloxy)succinimide, and N-(trifluoromethanesulfonyloxy)naphthalimide.

[0045] Examples of the disulfonyldiazomethane compound include bis(trifluoromethylsulfonyl)diazomethane, bis(cyclohexylsulfonyl)diazomethane, bis(phenylsulfonyl)diazomethane, bis(p-toluenesulfonyl)diazomethane, bis(2,4-dimethylbenzenesulfonyl)diazomethane, and methylsulfonyl-p-toluenesulfonyldiazomethane.

[0046] The acid generators may be used alone or in combination of two or more. When an acid generator is used, the proportion thereof is 0.01 to 10 parts by mass, or 0.1 to 8 parts by mass, or 0.5 to 5 parts by mass, relative to 100 parts by mass of the solid content of the nanoimprint resist underlayer film forming composition.

[0047] The nanoimprint resist underlayer film forming composition according to the present invention may contain optional components other than those described above. Each component will be described below.

[0048] [Other ingredients] The nanoimprint resist underlayer film forming composition of the present invention can be blended with a surfactant in order to further improve the coating property against surface unevenness without the occurrence of pinholes, striations, etc. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether, polyoxyethylene alkyl allyl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether, polyoxyethylene-polyoxypropylene block copolymers, sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate ... Examples of suitable surfactants include nonionic surfactants such as polyoxyethylene sorbitan fatty acid esters, such as polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate; fluorosurfactants such as F-TOP EF301, EF303, and EF352 (trade names, manufactured by Tochem Products Co., Ltd.), Megafac F171, F173, R-40, R-40N, and R-40LM (trade names, manufactured by DIC Corporation); Fluorad FC430 and FC431 (trade names, manufactured by Sumitomo 3M Limited); Asahiguard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, and SC106 (trade names, manufactured by Asahi Glass Co., Ltd.); and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.). The amount of these surfactants to be added is usually 2.0% by mass or less, and preferably 1.0% by mass or less, based on the total solid content of the resist underlayer film-forming composition. These surfactants may be used alone or in combination of two or more.When a surfactant is used, the proportion thereof is 0.0001 to 5 parts by mass, or 0.001 to 1 part by mass, or 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the solids content of the nanoimprint resist underlayer film forming composition.

[0049] The nanoimprint resist underlayer film forming composition of the present invention may contain a light absorbing agent, a rheology control agent, an adhesion promoter, etc. The rheology control agent is effective in improving the fluidity of the underlayer film forming composition. The adhesion promoter is effective in improving the adhesion between the semiconductor substrate or resist and the underlayer film.

[0050] Examples of the light absorbing agent include commercially available light absorbing agents described in "Technology and Market of Industrial Dyes" (CMC Publishing) and "Dye Handbook" (edited by the Society of Organic Synthesis Chemistry), such as CI Disperse Yellow 1, 3, 4, 5, 7, 8, 13, 23, 31, 49, 50, 51, 54, 60, 64, 66, 68, 79, 82, 88, 90, 93, 102, 114 and 124; CI Disperse Orange 1, 5, 13, 25, 29, 30, 31, 44, 57, 72 and 73; CI Disperse Red 1, 5, 7, 13, 17, 19, 43, 50, 54, 58, 65, 72, 73, 88, 117, 137, 143, 199 and 210; CI Disperse Violet 43; CI Disperse Blue 96; CI Fluorescent Brightening Agent Suitable examples of the light absorbing agent that can be used include 112, 135, and 163; CI Solvent Orange 2 and 45; CI Solvent Red 1, 3, 8, 23, 24, 25, 27, and 49; CI Pigment Green 10; and CI Pigment Brown 2. The light absorbing agent is usually blended in an amount of 10% by mass or less, and preferably 5% by mass or less, based on the total solid content of the nanoimprint resist underlayer film forming composition.

[0051] The rheology control agent is added mainly to improve the flowability of the nanoimprint resist underlayer film forming composition, and to improve the film thickness uniformity of the resist underlayer film and the filling ability of the nanoimprint resist underlayer film forming composition into the hole, especially in the baking process. Specific examples include phthalic acid derivatives such as dimethyl phthalate, diethyl phthalate, diisobutyl phthalate, dihexyl phthalate, and butyl isodecyl phthalate, adipic acid derivatives such as di-n-butyl adipate, diisobutyl adipate, diisooctyl adipate, and octyl decyl adipate, maleic acid derivatives such as di-n-butyl maleate, diethyl maleate, and dinonyl maleate, oleic acid derivatives such as methyl oleate, butyl oleate, and tetrahydrofurfuryl oleate, and stearic acid derivatives such as normal butyl stearate and glyceryl stearate. These rheology control agents are usually blended at a ratio of less than 30% by mass based on the total solid content of the nanoimprint resist underlayer film forming composition.

[0052] The adhesion promoter is added mainly for the purpose of improving the adhesion between the substrate or resist and the nanoimprint resist underlayer film forming composition, and in particular for the purpose of preventing the resist from peeling off during development. Specific examples include chlorosilanes such as trimethylchlorosilane, dimethylmethylolchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylmethylolethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole; methyloltrimethylsilane; and methyloltrimethylsilane. Examples of the adhesive auxiliary include silanes such as chlorosilane, γ-chloropropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane, heterocyclic compounds such as benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, urazole, thiouracil, mercaptoimidazole, and mercaptopyrimidine, and ureas such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. These adhesive auxiliary agents are usually blended in an amount of less than 5% by mass, preferably less than 2% by mass, based on the total solid content of the nanoimprint resist underlayer film-forming composition.

[0053] The solid content of the resist underlayer film forming composition for nanoimprinting according to the present invention is usually 0.1 to 70 mass%, preferably 0.1 to 60 mass%. The solid content is the content of all components excluding the solvent from the resist underlayer film forming composition for nanoimprinting. The proportion of the polymer in the solid content is preferably 1 to 100 mass%, 1 to 99.9 mass%, 50 to 99.9 mass%, 50 to 95 mass%, and 50 to 90 mass%, in that order.

[0054] One measure for evaluating whether a resist underlayer film-forming composition for nanoimprints is in a uniform solution state is to observe its passability through a specific microfilter. The resist underlayer film-forming composition for nanoimprints according to the present invention passes through a microfilter having a pore size of 0.1 μm and exhibits a uniform solution state.

[0055] Examples of the microfilter material include fluororesins such as PTFE (polytetrafluoroethylene) and PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer), PE (polyethylene), UPE (ultra-high molecular weight polyethylene), PP (polypropylene), PSF (polysulfone), PES (polyethersulfone), and nylon, with PTFE (polytetrafluoroethylene) being preferred.

[0056] The novolak resin having a repeating unit structure represented by formula (1) according to the present invention is blended with a solvent and other optional components to prepare a resist underlayer film-forming composition for nanoimprinting, which shows a contact angle with pure water of 65° or more when applied to a substrate (silicon wafer) and baked at 350°C.

[0057] Hereinafter, a method for producing a resist underlayer film, a method for forming a pattern, and a method for producing a semiconductor device using the resist underlayer film forming composition for nanoimprints according to the present invention will be described.

[0058] [Method of manufacturing nanoimprint resist underlayer film] The resist underlayer film forming composition for nanoimprinting of the present invention is applied onto a substrate (e.g., a silicon wafer substrate, a silicon / silicon dioxide-coated substrate, a silicon nitride substrate, a glass substrate, an ITO substrate, a polyimide substrate, and a substrate coated with a low dielectric constant material (low-k material)) used in the manufacture of a semiconductor device by a suitable application method such as a spinner or a coater, and then baked to form a resist underlayer film. The baking conditions are appropriately selected from a baking temperature of 80°C to 400°C and a baking time of 0.3 to 60 minutes. Preferably, the baking temperature is 150°C to 350°C and the baking time is 0.5 to 2 minutes. Here, the thickness of the underlayer film formed is, for example, 10 to 1000 nm, or 20 to 500 nm, or 30 to 400 nm, or 50 to 300 nm. In addition, if a quartz substrate is used as the substrate, a replica (mold replica) of a quartz imprint mold can be produced.

[0059] Also, an adhesion layer and / or a silicone layer containing 99% by mass or less or 50% by mass or less of Si can be formed by coating or vapor deposition on the nanoimprint resist underlayer film according to the present invention. For example, in addition to a method of forming an adhesion layer described in JP2013-202982A or JP5827180A or a method of forming a silicon-containing resist underlayer film (inorganic resist underlayer film) forming composition described in WO2009 / 104552A1 by spin coating, a Si-based inorganic material film can be formed by a CVD method or the like.

[0060] Furthermore, by applying the resist underlayer film forming composition for nanoimprints according to the present invention onto a semiconductor substrate having a portion with a step and a portion without a step (a so-called stepped substrate), and baking the substrate, a resist underlayer film can be formed in which the step between the portion with the step and the portion without the step is within the range of 3 to 70 nm.

[0061] [Pattern formation method] The pattern forming method according to the present invention comprises the steps of: A step of applying a curable composition onto the resist underlayer film formed by the method for producing a resist underlayer film according to the present invention; contacting the curable composition with a mold; A step of irradiating the curable composition with light or an electron beam to form a cured film; and A step of separating the cured film from the mold; Includes.

[0062] [Curable composition] The photoresist formed on the resist underlayer film is not particularly limited as long as it is sensitive to the light used for exposure. Either negative photoresist or positive photoresist can be used. There are positive photoresists made of novolac resin and 1,2-naphthoquinone diazide sulfonic acid ester, chemically amplified photoresists made of a binder having a group that decomposes with acid to increase the alkaline dissolution rate and a photoacid generator, chemically amplified photoresists made of a low molecular compound that decomposes with acid to increase the alkaline dissolution rate of the photoresist, an alkali-soluble binder, and a photoacid generator, and chemically amplified photoresists made of a binder having a group that decomposes with acid to increase the alkaline dissolution rate, a low molecular compound that decomposes with acid to increase the alkaline dissolution rate of the photoresist, and a photoacid generator. Examples of such photoresists include APEX-E (trade name) manufactured by Shipley, PAR710 (trade name) manufactured by Sumitomo Chemical Co., Ltd., and SEPR430 (trade name) manufactured by Shin-Etsu Chemical Co., Ltd. Further, there can be mentioned fluorine-containing polymer photoresists as described in, for example, Proc. SPIE, Vol. 3999, 330-334 (2000), Proc. SPIE, Vol. 3999, 357-364 (2000), and Proc. SPIE, Vol. 3999, 365-374 (2000).

[0063] [Step of applying the curable composition] This step is a step of applying a curable composition onto the resist underlayer film formed by the method for producing a resist underlayer film according to the present invention. For example, an inkjet method, a dip coating method, an air knife coating method, a curtain coating method, a wire bar coating method, a gravure coating method, an extrusion coating method, a spin coating method, a slit scan method, etc. can be used as a method for applying the curable composition. The inkjet method is suitable for applying the curable composition as droplets, and the spin coating method is suitable for applying the curable composition. In this step, an adhesion layer and / or a silicone layer containing 99% by mass or less or 50% by mass or less of Si can be formed on the resist underlayer film by coating or vapor deposition, and the curable composition can be applied thereon.

[0064] [Step of contacting the curable composition with the mold] In this step, the curable composition is brought into contact with a mold. For example, when the liquid curable composition is brought into contact with a mold having a prototype pattern for transferring a pattern shape, a liquid film is formed in which the curable composition fills the recesses of the fine pattern on the mold surface.

[0065] Considering the process of irradiating light or electron beams described later, it is recommended to use a mold having a light-transmitting material as a substrate. Specifically, the mold substrate is preferably glass, quartz, light-transmitting resin such as PMMA or polycarbonate resin, transparent metal deposition film, flexible film such as polydimethylsiloxane, photocured film, metal film, etc. The mold substrate is more preferably quartz because of its small thermal expansion coefficient and small pattern distortion.

[0066] The fine pattern on the surface of the mold preferably has a pattern height of 4 nm or more and 200 nm or less. A certain pattern height is necessary to increase the processing accuracy of the substrate, but the lower the pattern height, the lower the force required to peel the mold from the cured film in the process of separating the cured film and the mold described below, and the fewer defects remaining on the mask side after the resist pattern is torn off. Taking these factors into consideration, it is recommended to select and adopt a pattern height with an appropriate balance. In addition, when the mold is peeled off, the elastic deformation of the resist pattern due to the impact can cause adjacent resist patterns to come into contact with each other, resulting in adhesion or damage to the resist patterns. This can sometimes be avoided by making the pattern height approximately twice the pattern width (aspect ratio 2 or less).

[0067] In order to improve the releasability between the curable composition and the surface of the mold, the mold may be subjected to a surface treatment in advance. As a method of surface treatment, a method of applying a release agent to the surface of the mold to form a release agent layer may be mentioned. As the release agent, a silicone-based release agent, a fluorine-based release agent, a hydrocarbon-based release agent, a polyethylene-based release agent, a polypropylene-based release agent, a paraffin-based release agent, a montan-based release agent, a carnauba-based release agent, etc. may be mentioned. Fluorine-based and hydrocarbon-based release agents are preferable. As a commercially available product, for example, Optool (registered trademark) DSX manufactured by Daikin Industries, Ltd. may be mentioned. The release agent may be used alone or in combination of two or more kinds.

[0068] In this step, the pressure applied to the curable composition when the mold and the curable composition are brought into contact with each other is not particularly limited. A pressure of 0 MPa or more and 100 MPa or less is recommended. The pressure is preferably 0 MPa or more and 50 MPa or less, 30 MPa or less, or 20 MPa or less.

[0069] If the pre-spreading of the droplets of the curable composition has progressed in the previous step (the step of applying the curable composition), the spreading of the curable composition in this step is completed quickly. As a result, the time for contacting the mold with the curable composition can be shortened. The contact time is not particularly limited, but is preferably 0.1 seconds or more and 600 seconds or less, 3 seconds or less, or 1 second or less. If the contact time is too short, the spreading and filling may be insufficient, and a defect called an unfilled defect may occur.

[0070] This step can be carried out under any of the conditions of air atmosphere, reduced pressure atmosphere, and inert gas atmosphere, but is preferably carried out under a pressure of 0.0001 atm or more and 10 atm or less. In order to prevent the influence of oxygen and moisture on the curing reaction, it is recommended to carry out the step under a reduced pressure atmosphere or in an inert gas atmosphere. Specific examples of inert gases that can be used to create an inert gas atmosphere include nitrogen, carbon dioxide, helium, argon, CFC, HCFC, HFC, and mixed gases thereof.

[0071] This step may be performed under an atmosphere containing a condensable gas (hereinafter referred to as a "condensable gas atmosphere"). In this specification, the condensable gas refers to a gas that is condensed and liquefied by the capillary pressure generated when the gas is filled into the recesses of the fine pattern formed on the mold and the gap between the mold and the substrate together with the curable composition. The condensable gas exists as a gas in the atmosphere before the curable composition comes into contact with the mold in this step. When this step is performed under a condensable gas atmosphere, the gas filled into the recesses of the fine pattern is liquefied by the capillary pressure generated by the curable composition, and the bubbles disappear, resulting in excellent filling properties. The condensable gas may be dissolved in the curable composition.

[0072] The boiling point of the condensable gas is not limited as long as it is equal to or lower than the atmospheric temperature in this step, but is preferably -10°C or higher, or +10°C or higher and +23°C or lower.

[0073] The vapor pressure of the condensable gas at the atmospheric temperature in this step is not particularly limited as long as it is equal to or lower than the mold pressure, and is preferably in the range of 0.1 MPa to 0.4 MPa.

[0074] Specific examples of condensable gases include chlorofluorocarbons (CFCs) such as trichlorofluoromethane, fluorocarbons (FCs), hydrochlorofluorocarbons (HCFCs), hydrofluorocarbons (HFCs) such as 1,1,1,3,3-pentafluoropropane (CHF2CH2CF3, HFC-245fa, PFP), and hydrofluoroethers (HFEs) such as pentafluoroethyl methyl ether (CF3CF2OCH3, HFE-245mc).

[0075] The condensable gas may be used alone or in combination of two or more. The condensable gas may be used in combination with a non-condensable gas such as air, nitrogen, carbon dioxide, helium, argon, etc. Air and helium are preferred as non-condensable gases to be mixed with the condensable gas.

[0076] [Step of irradiating the curable composition with light or electron beam to form a cured film] In this step, the curable composition is irradiated with light or an electron beam to form a cured film. That is, the curable composition filled in the fine pattern of the mold is irradiated with light or an electron beam through the mold, and the curable composition filled in the fine pattern of the mold is cured in that state to form a cured film having a pattern shape.

[0077] The light or electron beam is selected according to the sensitivity wavelength of the curable composition. Specifically, ultraviolet light, X-rays, electron beams, etc. having a wavelength of 150 nm or more and 400 nm or less can be appropriately selected and used. Examples of light or electron beam light sources include high pressure mercury lamps, ultra-high pressure mercury lamps, low pressure mercury lamps, Deep-UV lamps, carbon arc lamps, chemical lamps, metal halide lamps, xenon lamps, KrF excimer lasers, ArF excimer lasers, F2 excimer lasers, etc. The number of light sources may be one or more. Irradiation may be performed on the entire curable composition filled in the fine pattern of the mold, or only on a partial area. Light irradiation may be performed intermittently multiple times on the entire area on the substrate, or may be continuously irradiated on the entire area. In addition, a first irradiation may be performed on a partial area on the substrate, and a second irradiation may be performed on an area different from the partial area.

[0078] The cured film thus obtained preferably has a pattern with a size of 1 nm or more, or 10 nm or more, and 10 mm or less, or 100 μm or less.

[0079] [Step of separating the cured film from the mold] In this step, the cured film is separated from the mold. The patterned cured film is separated from the mold to obtain a free-standing cured film having a pattern that is a reverse pattern of the fine pattern formed on the mold.

[0080] The method for separating the cured film having a pattern shape from the mold is not particularly limited as long as it is a means for moving the cured film and the mold in a direction in which they are relatively separated from each other, as long as a part of the cured film having a pattern shape is not physically damaged, and various conditions are also not particularly limited. For example, the substrate may be fixed and the mold may be moved away from the substrate to be peeled off, or the mold may be fixed and the substrate may be moved away from the mold to be peeled off. Alternatively, the substrate and the mold may be pulled and moved in opposite directions to be peeled off.

[0081] In addition, when the above-mentioned step of contacting the curable composition with the mold is carried out in a condensable gas atmosphere, when the cured film is separated from the mold in this step, the pressure at the interface where the cured film and the mold are in contact with each other decreases, and the condensable gas evaporates, which makes it possible to reduce the release force required to separate the cured film from the mold.

[0082] By the above steps, a cured film having a desired concave-convex pattern shape derived from the concave-convex shape of the mold at desired positions can be prepared.

[0083] [Method of manufacturing semiconductor device] The inorganic underlayer film (middle layer) is removed using the pattern of the photoresist (upper layer) formed by the patterning method of the present invention as a protective film, and then the organic underlayer film (lower layer) is removed using the film consisting of the patterned photoresist and the inorganic underlayer film (middle layer) as a protective film. Finally, the semiconductor substrate is processed using the patterned inorganic underlayer film (middle layer) and the organic underlayer film (lower layer) as protective films.

[0084] First, the inorganic underlayer film (intermediate layer) in the portion where the photoresist has been removed is removed by dry etching to expose the semiconductor substrate. For dry etching of the inorganic underlayer film, gases such as tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, carbon monoxide, argon, oxygen, nitrogen, sulfur hexafluoride, difluoromethane, nitrogen trifluoride, chlorine trifluoride, chlorine, trichloroborane, and dichloroborane can be used. For dry etching of the inorganic underlayer film, it is preferable to use a halogen-based gas, and more preferable to use a fluorine-based gas. Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).

[0085] Thereafter, the organic underlayer film is removed using the patterned photoresist and the inorganic underlayer film as a protective film. The organic underlayer film (underlayer) is preferably removed by dry etching with an oxygen-based gas. This is because the inorganic underlayer film, which contains a large amount of silicon atoms, is difficult to remove by dry etching with an oxygen-based gas.

[0086] Finally, the semiconductor substrate is processed, preferably by dry etching using a fluorine-based gas. Examples of fluorine-based gases include tetrafluoromethane (CF4), perfluorocyclobutane (C4F8), perfluoropropane (C3F8), trifluoromethane, and difluoromethane (CH2F2).

[0087] An organic anti-reflective coating can be formed on the resist underlayer before the formation of the photoresist. The anti-reflective coating composition used therein is not particularly limited, and can be arbitrarily selected from those conventionally used in the lithography process, and the anti-reflective coating can be formed by a conventional method, for example, coating with a spinner or coater and baking.

[0088] In the present invention, an organic underlayer film is formed on a substrate, and then an inorganic underlayer film is formed thereon, and a photoresist is further coated thereon. This narrows the pattern width of the photoresist, and even if the photoresist is thinly coated to prevent pattern collapse, the substrate can be processed by selecting an appropriate etching gas. For example, a fluorine-based gas that has a sufficiently high etching rate for the photoresist can be used as an etching gas to process the resist underlayer film, a fluorine-based gas that has a sufficiently high etching rate for the inorganic underlayer film can be used as an etching gas to process the substrate, and an oxygen-based gas that has a sufficiently high etching rate for the organic underlayer film can be used as an etching gas to process the substrate.

[0089] The resist underlayer film formed from the resist underlayer film forming composition may also have absorption of light depending on the wavelength of the light used in the lithography process. In such a case, it can function as an anti-reflective film having the effect of preventing reflected light from the substrate. Furthermore, the underlayer film formed from the resist underlayer film forming composition of the present invention can also function as a hard mask. The underlayer film of the present invention can also be used as a layer for preventing interaction between the substrate and the photoresist, a layer having a function of preventing the adverse effect on the substrate of the material used in the photoresist or the substance generated during exposure to the photoresist, a layer having a function of preventing the diffusion of the substance generated from the substrate during heating and baking into the upper photoresist, and a barrier layer for reducing the poisoning effect of the photoresist layer due to the dielectric layer of the semiconductor substrate.

[0090] In addition, the underlayer film formed from the resist underlayer film forming composition can be applied to a substrate having a via hole used in a dual damascene process, and can be used as a filling material capable of filling the hole without gaps. Also, the composition can be used as a planarizing material for planarizing the surface of a semiconductor substrate having irregularities. EXAMPLES

[0091] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these.

[0092] The weight average molecular weight of the resin (polymer) obtained in the following Synthesis Example 1 is a result of measurement by gel permeation chromatography (hereinafter abbreviated as GPC). For the measurement, a GPC device manufactured by Tosoh Corporation was used, and the measurement conditions are as follows. GPC columns: Shodex KF803L, Shodex KF802, Shodex KF801 (registered trademark) (Showa Denko K.K.) Column temperature: 40℃ Solvent: Tetrahydrofuran (THF) Flow rate: 1.0ml / min Standard sample: Polystyrene (manufactured by Tosoh Corporation)

[0093] The etcher and etching gas used in the measurement of the dry etching rate were as follows: RIE-10NR (Samco): CF4

[0094] [Synthesis Example 1] In a 100 mL two-neck flask, 9.71 g of 4-tert-butylbenzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 48.68 g of propylene glycol monomethyl ether acetate (hereinafter referred to as PGMEA), and 1.15 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for 30 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was subjected to suction filtration, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-1). The weight average molecular weight Mw measured in terms of polystyrene by GPC was 4,900. [ka]

[0095] [Synthesis Example 2] In a 100 mL two-neck flask, 10.42 g of 4-(trifluoromethyl)-benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 50.34 g of PGMEA, and 1.15 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 3.5 hours. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-2). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 4,200. [ka]

[0096] [Synthesis Example 3] In a 100 mL two-neck flask, 8.39 g of 4-tert-butylbenzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of 2-phenylindole (Tokyo Chemical Industry Co., Ltd.), 45.24 g of PGMEA, and 0.99 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 17 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-3). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,200. [ka]

[0097] [Synthesis Example 4] In a 100 mL two-neck flask, 9.01 g of 4-(trifluoromethyl)-benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of 2-phenylindole (Tokyo Chemical Industry Co., Ltd.), 46.68 g of PGMEA, and 0.99 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 17 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-4). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,200. [ka]

[0098] [Synthesis Example 5] In a 100 mL two-neck flask, 7.40 g of 4-tert-butylbenzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of N-phenyl-1-naphthylamine (Tokyo Chemical Industry Co., Ltd.), 18.50 g of PGMEA, and 1.10 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for 10 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-5). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 6,000. [ka]

[0099] [Synthesis Example 6] In a 100 mL two-neck flask, 7.95 g of 4-(trifluoromethyl)-benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of N-phenyl-1-naphthylamine (Tokyo Chemical Industry Co., Ltd.), 18.50 g of PGMEA, and 0.55 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for 10 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-6). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 30,000. [ka]

[0100] [Synthesis Example 7] In a 100mL two-neck flask, 4.63g of 4-tert-butylbenzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00g of 9,9-bis(4-hydroxyphenyl)fluorene (Tokyo Chemical Industry Co., Ltd.), 22.77g of PGMEA, and 0.55g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 5.5 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-7). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 2,000. [ka]

[0101] [Synthesis Example 8] In a 100mL two-neck flask, 4.97g of 4-(trifluoromethyl)-benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00g of 9,9-bis(4-hydroxyphenyl)fluorene (Tokyo Chemical Industry Co., Ltd.), 23.28g of PGMEA, and 0.55g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 5.5 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-8). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 10,000. [ka]

[0102] [Synthesis Example 9] In a 100mL two-neck flask, 10.13g of 4-tert-butylbenzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00g of 1,5-dihydroxynaphthalene (Tokyo Chemical Industry Co., Ltd.), 49.77g of PGMEA, and 1.20g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 1 hour and 45 minutes. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-9). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,200. [ka]

[0103] [Synthesis Example 10] In a 100mL two-neck flask, 10.87g of 4-(trifluoromethyl)-benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00g of 1,5-dihydroxynaphthalene (Tokyo Chemical Industry Co., Ltd.), 51.50g of PGMEA, and 1.20g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed for 2 hours and 15 minutes with stirring. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-10). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 8,300. [ka]

[0104] [Synthesis Example 11] In a 100 mL two-neck flask, 4.69 g of 4-tert-butylbenzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of bisphenol M (Tokyo Chemical Industry Co., Ltd.), 35.56 g of PGMEA, and 0.56 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 16 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-11). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 8,000. [ka]

[0105] [Synthesis Example 12] In a 100 mL two-neck flask, 5.03 g of 4-(trifluoromethyl)-benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of bisphenol M (Tokyo Chemical Industry Co., Ltd.), 36.36 g of PGMEA, and 0.56 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for 5 hours. After the reaction was completed, the solution was dropped into a methanol / water mixture to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (2-12). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 6,500. [ka]

[0106] [Comparative Synthesis Example 1] In a 100 mL two-neck flask, 6.35 g of benzaldehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 40.84 g of PGMEA, and 1.15 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for about 30 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-1). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 52,300. [ka]

[0107] [Comparative Synthesis Example 2] In a 100 mL two-neck flask, 5.49 g of benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of 2-phenylindole (Tokyo Chemical Industry Co., Ltd.), 16.49 g of PGMEA, and 0.99 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for about 5 hours. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-2). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 1,600. [ka]

[0108] [Comparative Synthesis Example 3] In a 100 mL two-neck flask, 4.84 g of benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of N-phenyl-1-naphthylamine (Tokyo Chemical Industry Co., Ltd.), 36.67 g of PGMEA, and 0.88 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for about 15 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-3). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,900. [ka]

[0109] [Comparative Synthesis Example 4] In a 100 mL two-neck flask, 3.03 g of benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of 9,9-bis(4-hydroxyphenyl)fluorene (Tokyo Chemical Industry Co., Ltd.), 32.68 g of PGMEA, and 0.55 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for about 17.5 hours. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-4). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 10,300. [ka]

[0110] [Comparative Synthesis Example 5] In a 100 mL two-neck flask, 6.62 g of benzaldehyde (Tokyo Chemical Industry Co., Ltd.), 10.00 g of 1,5-dihydroxynaphthalene (Tokyo Chemical Industry Co., Ltd.), 41.58 g of PGMEA, and 1.20 g of methanesulfonic acid (Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed with stirring for about 1.5 hours. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-5). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,300. [ka]

[0111] [Comparative Synthesis Example 6] In a 100 mL two-neck flask, 7.19 g of p-tolualdehyde (manufactured by Tokyo Chemical Industry Co., Ltd.), 10.00 g of carbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 42.80 g of PGMEA, and 1.15 g of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were placed. The mixture was then heated to 150°C and refluxed and stirred for about 30 minutes. After the reaction was completed, the solution was dropped into methanol to cause reprecipitation. The resulting precipitate was filtered by suction, and the residue was dried under reduced pressure at 60°C overnight. The resulting polymer corresponded to formula (1-6). The weight average molecular weight Mw measured by GPC in terms of polystyrene was 5,900. [ka]

[0112] The chemical structures (examples) and abbreviations of the raw materials used in the examples are as follows: [ka] [ka]

[0113] [Example 1] The resin obtained in Synthesis Example 1 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0114] [Example 2] The resin obtained in Synthesis Example 2 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0115] [Example 3] The resin obtained in Synthesis Example 3 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0116] [Example 4] The resin obtained in Synthesis Example 4 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0117] [Example 5] The resin obtained in Synthesis Example 5 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0118] [Example 6] The resin obtained in Synthesis Example 6 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0119] [Example 7] The resin obtained in Synthesis Example 7 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0120] [Example 8] The resin obtained in Synthesis Example 8 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0121] [Example 9] The resin obtained in Synthesis Example 9 was dissolved in propylene glycol monomethyl ether (hereinafter, referred to as PGME), and then subjected to ion exchange to obtain a resin solution (solid content: 22.6% by mass). PGME was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0122] [Example 10] The resin obtained in Synthesis Example 10 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0123] [Example 11] The resin obtained in Synthesis Example 11 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0124] [Example 12] The resin obtained in Synthesis Example 12 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.6% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0125] [Example 13] The resin obtained in Synthesis Example 1 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 22.6% by mass). 0.12g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.09g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.45g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.34g of PGMEA, and 2.35g of PGME were added to 2.65g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0126] [Example 14] The resin obtained in Synthesis Example 2 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 20.1% by mass). 0.12 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.09 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.34 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.00 g of PGMEA, and 2.49 g of PGME were added to 3.00 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0127] [Example 15] The resin obtained in Synthesis Example 3 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 19.0% by mass). 0.07g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.18g of PGME-BIP-A (manufactured by Finechem Co., Ltd.), 0.46g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 2.91g of PGMEA, and 1.43g of PGME were added to 1.94g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0128] [Example 16] The resin obtained in Synthesis Example 4 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 20.8% by mass). 0.08 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.06 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.31 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 2.88 g of PGMEA, and 1.64 g of PGME were added to 2.02 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0129] [Example 17] The resin obtained in Synthesis Example 5 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 19.1% by mass). 0.12g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.19g of PGME-BIP-A (manufactured by Finechem Co., Ltd.), 0.43g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 3.96g of PGMEA, and 2.29g of PGME were added to 3.01g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0130] [Example 18] The resin obtained in Synthesis Example 6 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 20.5% by mass). 0.12 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.09 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.45 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.07 g of PGMEA, and 2.35 g of PGME were added to 2.92 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0131] [Example 19] The resin obtained in Synthesis Example 7 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 22.2% by mass). 0.11 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.11 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.85 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.41 g of PGMEA, and 1.95 g of PGME were added to 2.56 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0132] [Example 20] The resin obtained in Synthesis Example 8 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 22.8% by mass). 0.11 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.11 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.85 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.47 g of PGMEA, and 1.95 g of PGME were added to 2.49 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0133] [Example 21] The resin obtained in Synthesis Example 9 was dissolved in PGME, and then ion-exchanged to obtain a resin solution (solid content 19.7% by mass). 0.11 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.11 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.85 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 2.68 g of PGMEA, and 3.36 g of PGME were added to 2.88 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0134] [Example 22] The resin obtained in Synthesis Example 10 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 22.9% by mass). 0.11 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.11 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.85 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.48 g of PGMEA, and 1.95 g of PGME were added to 2.48 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0135] [Example 23] The resin obtained in Synthesis Example 11 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 17.9% by mass). 0.07 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.07 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.26 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 2.25 g of PGMEA, and 1.42 g of PGME were added to 1.93 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0136] [Example 24] The resin obtained in Synthesis Example 12 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 17.8% by mass). 0.12 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.12 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.43 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 3.73 g of PGMEA, and 2.37 g of PGME were added to 3.24 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0137] [Comparative Example 1] The resin obtained in Comparative Synthesis Example 1 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 18.4% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0138] [Comparative Example 2] The resin obtained in Comparative Synthesis Example 2 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 22.5% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0139] [Comparative Example 3] The resin obtained in Comparative Synthesis Example 3 was dissolved in cyclohexanone, and then subjected to ion exchange to obtain a resin solution (solid content: 17.7% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0140] [Comparative Example 4] The resin obtained in Comparative Synthesis Example 4 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 15.9% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0141] [Comparative Example 5] The resin obtained in Comparative Synthesis Example 5 was dissolved in PGME, and then ion-exchanged to obtain a resin solution (solid content: 18.2% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0142] [Comparative Example 6] The resin obtained in Comparative Synthesis Example 6 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content: 26.0% by mass). PGMEA was added and mixed so that the resin solid content became 5%, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0143] [Comparative Example 7] The resin obtained in Comparative Synthesis Example 6 was dissolved in PGMEA, and then ion-exchanged to obtain a resin solution (solid content 22.6% by mass). 0.11 g of PGMEA containing 1% by mass of surfactant (MEGAFAC R-40, manufactured by DIC Corporation), 0.11 g of TMOM-BP (manufactured by Honshu Chemical Industry Co., Ltd.), 0.85 g of PGME containing 2% by mass of pyridinium p-hydroxybenzenesulfonate (Tokyo Chemical Industry Co., Ltd.), 4.78 g of PGMEA, and 1.95 g of PGME were added to 2.19 g of this resin solution and dissolved, and the mixture was filtered through a polytetrafluoroethylene microfilter having a pore size of 0.1 μm to prepare a solution of a resist underlayer film-forming composition.

[0144] (Polymer contact angle measurement) The solutions of the resist underlayer film forming compositions prepared in Examples 1-12 and Comparative Examples 1-6 were applied onto silicon wafers using a spin coater, and baked on a hot plate at 240° C. for 60 seconds or at 350° C. for 60 seconds to form polymer films. Thereafter, the contact angle of the polymer with pure water was measured using a contact angle meter manufactured by Kyowa Interface Science Co., Ltd.

[0145] [Table 1]

[0146] As mentioned above, novolac resins with tert-butyl or trifluoromethyl groups have a distinct advantage over similar skeletons in that they exhibit a specifically high pure water contact angle (= hydrophobicity) not only when baked at low temperatures but also when baked at high temperatures. In the next section, we will show the evaluation results of the physical properties of materials made by mixing a novolac resin with tert-butyl or trifluoromethyl groups with a crosslinker, an acid catalyst, and a surfactant.

[0147] (Contact angle measurement of materials) The solutions of the resist underlayer film forming compositions prepared in Examples 13-24 and Comparative Example 7 were each applied onto a silicon wafer using a spin coater, and baked on a hot plate at 350° C. for 60 seconds to form a 200 nm resist underlayer film. Thereafter, the contact angle with respect to pure water was measured using a contact angle meter manufactured by Kyowa Interface Science Co., Ltd.

[0148] [Table 2]

[0149] As mentioned above, novolac resins having tert-butyl or trifluoromethyl groups exhibit a uniquely high contact angle with pure water (=hydrophobicity) when baked at high temperatures, even when used as materials. This makes it possible to increase adhesion with a hydrophobic upper layer film, and is also expected to exhibit good permeability to hydrophobic gases.

[0150] (Elution test in resist solvent) The solutions of the resist underlayer film forming compositions prepared in Examples 13-24 and Comparative Example 7 were each applied onto a silicon wafer using a spin coater, and baked on a hot plate at 350°C for 60 seconds to form resist underlayer films (film thickness 0.20 µm). These resist underlayer films were immersed in ethyl lactate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and cyclohexanone, which are solvents used in resists. These resist underlayer films were insoluble in these solvents.

[0151] (Optical constant measurement) The solutions of the resist underlayer film forming compositions prepared in Examples 13-24 and Comparative Example 7 were each applied onto a silicon wafer using a spin coater. The resist underlayer films were baked on a hot plate at 350° C. for 60 seconds to form resist underlayer films (film thickness 0.05 μm). The refractive index (n value) and optical extinction coefficient (k value, also called extinction coefficient) of these resist underlayer films at a wavelength of 193 nm were measured using a spectroscopic ellipsometer (Table 3).

[0152] [Table 3]

[0153] As described above, the optical constants of the novolak resin having a tert-butyl group or a trifluoromethyl group can be adjusted to suit the process by changing the molecular skeleton.

[0154] [Dry etching rate measurement] The solutions of the resist underlayer film forming compositions prepared in Examples 13-24 and Comparative Example 7 were each applied onto a silicon wafer using a spin coater. The resist underlayer film (film thickness 0.20 μm) was formed by baking on a hot plate at 350° C. for 60 seconds. The dry etching rates were measured using CF4 gas as the etching gas, and the dry etching rate ratios of Examples 13-24 and Comparative Example 7 were calculated. The dry etching rate ratio is the dry etching rate ratio of (resist underlayer film) / (KrF photoresist) (Table 4).

[0155] [Table 4]

[0156] As described above, the etching rate of the novolak resin having a tert-butyl group or a trifluoromethyl group can be adjusted to suit the process by changing the molecular skeleton.

[0157] (Coating test for stepped substrate) As a coating test for a stepped substrate, a comparison was made between the coating thickness of an 800 nm trench area (TRENCH) and an open area (OPEN) where no pattern was formed on a 200 nm thick SiO2 substrate. The resist underlayer film forming compositions prepared in Examples 13-24 and Comparative Example 7 were applied to the substrate, and then baked at 350°C for 60 seconds to form a resist underlayer film of about 200 nm. The planarization of this substrate was observed using a scanning electron microscope (S-4800) manufactured by Hitachi High-Technologies Corporation, and the planarization was evaluated by measuring the film thickness difference (the coating step between the trench area and the open area, which is called the bias) between the trench area (patterned portion) and the open area (no pattern portion) of the stepped substrate. Here, the planarization means that the film thickness difference (Iso-TRENCH bias) of the coating material present on the upper portion between the portion where the pattern exists (TRENCH (patterned portion)) and the portion where the pattern does not exist (open area (no pattern)) is small (Table 5). Examples in which an improvement of less than 10 nm was confirmed compared to the comparative example were rated as △, examples in which an improvement of 10 nm or more was confirmed were rated as ○, and examples in which an improvement of 20 nm or more was confirmed compared to the comparative example were rated as ◎.

[0158] [Table 5]

[0159] As described above, the novolak resin having a tert-butyl group or a trifluoromethyl group exhibits good planarization properties. [Industrial Applicability]

[0160] The novolac resin according to the present invention exhibits a specifically high pure water contact angle (=hydrophobicity) not only when baked at a low temperature but also when baked at a high temperature. In addition, the novolac resin according to the present invention exhibits a specifically high pure water contact angle (=hydrophobicity) when baked at a high temperature, even when mixed with a crosslinker, an acid catalyst, and a surfactant to form a material. Furthermore, the novolac resin according to the present invention exhibits good planarization properties, and by changing the molecular skeleton, the optical constants and etching speed can be adjusted to suit the process.

Claims

1. The following formula (1): [Formula 1] [In formula (1), Group A represents an organic group having an aromatic ring, a condensed aromatic ring, or a condensed aromatic heterocycle; Group B represents an organic group having an aromatic ring or a condensed aromatic ring; The group E represents a single bond or a branched or linear alkylene group having 1 to 10 carbon atoms which may be substituted and which may contain an ether bond and / or a carbonyl group; Group D is [chemical 2] (In the formula, R 1 , R 2 , R 3 each independently represents a fluorine atom or a linear, branched, or cyclic alkyl group; R 1 , R 2 , R 3 Any two of the groups may be bonded to each other to form a ring. n represents a number from 1 to 5. A novolak resin having a repeating unit structure represented by the formula: The novolac resin contains a novolac resin that exhibits a contact angle with pure water of 76° or more when the resin is dissolved in a solvent, applied onto a substrate, and baked at 240° C., and exhibits a contact angle with pure water of 70° or more when baked at 350° C. A composition for forming a resist underlayer film for nanoimprinting.

2. 2. The resist underlayer film forming composition for nanoimprints according to claim 1, wherein the group D is a tert-butyl group or a trifluoromethyl group.

3. 3. The resist underlayer film forming composition for nanoimprints according to claim 1 or 2, wherein the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in Group A is an organic group having one or more benzene rings, naphthalene rings, anthracene rings, pyrene rings, or fused rings of a benzene ring and a heterocycle or an aliphatic ring.

4. 4. The resist underlayer film forming composition for nanoimprints according to claim 1, wherein the organic group having an aromatic ring, a fused aromatic ring, or a fused aromatic heterocycle in Group A is an organic group having 6 to 30 carbon atoms which may contain at least one heteroatom selected from N, S and O on, within, or between the rings.

5. The resist underlayer film forming composition for nanoimprints according to claim 1 , wherein the group A is at least one selected from the following: [C3] (In the formula, i, j, m, and n each independently represent 1 or 2. G represents a direct bond or any of the following formulae: [C4] L and M each independently represent a hydrogen atom, a phenyl group, or C 1-3 represents an alkyl group.

6. The resist underlayer film forming composition for nanoimprints according to claim 1 , wherein the group B is phenylene, biphenylene, naphthalenediyl, anthracenediyl, or phenanthrenediyl.

7. 7. The resist underlayer film forming composition for nanoimprints according to claim 1, wherein the group E is a single bond or a linear alkylene group having 1 to 6 carbon atoms.

8. The resist underlayer film forming composition for nanoimprints according to claim 1 , wherein the group E is a single bond.

9. The nanoimprint resist underlayer film forming composition according to claim 1, further comprising a crosslinking agent.

10. The following formula (1): [Formula 1] [In formula (1), Group A represents an organic group having an aromatic ring, a condensed aromatic ring, or a condensed aromatic heterocycle; Group B represents an organic group having an aromatic ring or a condensed aromatic ring; The group E represents a single bond or a branched or linear alkylene group having 1 to 10 carbon atoms which may be substituted and which may contain an ether bond and / or a carbonyl group; Group D is [chemical 2] (wherein R 1 , R 2 and R 3 each independently represent a fluorine atom or a linear, branched or cyclic alkyl group, and any two of R 1 , R 2 and R 3 may be bonded to each other to form a ring), n represents a number from 1 to 5. and a crosslinking agent, When baked at 350°C, it exhibits a contact angle of 65° or more with pure water. A composition for forming a resist underlayer film for nanoimprinting.

11. The resist underlayer film forming composition for nanoimprints according to claim 1 , further comprising at least one selected from the group consisting of an acid, a salt thereof, and an acid generator.

12. The resist underlayer film forming composition for nanoimprints according to claim 9 or 11, which exhibits a contact angle with pure water of 65° or more when baked at 350°C.

13. A resist underlayer film which is a cured product of a coating film comprising the resist underlayer film forming composition for nanoimprints according to claim 1 .

14. A method for producing a resist underlayer film, comprising applying the resist underlayer film forming composition for nanoimprints according to claim 1 onto a semiconductor substrate, and baking the applied resist underlayer film.

15. A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of claims 1 to 12; applying a curable composition onto the resist underlayer film; contacting the curable composition with a mold; A step of irradiating the curable composition with light or an electron beam to form a cured film; and A step of separating the cured film from the mold; A pattern forming method comprising the steps of:

16. The pattern formation method according to claim 15, wherein the step of applying a curable composition onto the resist underlayer film comprises forming an adhesion layer and / or a silicone layer containing 99% by mass or less of Si on the resist underlayer film by coating or vapor deposition, and applying a curable composition thereon.

17. A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of claims 1 to 12; forming a resist film thereon; A step of forming a resist pattern by irradiation with light or an electron beam and development; Etching the underlayer film using the formed resist pattern; and A process for processing a semiconductor substrate using a patterned underlayer film A method for manufacturing a semiconductor device comprising the steps of:

18. A step of forming a resist underlayer film on a semiconductor substrate from the resist underlayer film forming composition for nanoimprints according to any one of claims 1 to 12; forming a hard mask thereon; Further, a step of forming a resist film thereon; A step of forming a resist pattern by irradiation with light or an electron beam and development; Etching the hard mask using the formed resist pattern; Etching the underlayer film with a patterned hard mask; and A process for processing a semiconductor substrate using a patterned resist underlayer film. A method for manufacturing a semiconductor device comprising the steps of:

Citation Information

Patent Citations

  • Roller mold, base material for roller mold, and pattern transfer method

    JP2013035243A

  • Composition for forming film, film, method for manufacturing patterned substrate, and compound

    JP2016060886A

  • Pattern formation method

    JP2019036725A

  • Resist underlayer film forming composition containing substituted crosslinkable compound

    WO2014208542A1

  • Resist underlayer film forming composition containing triaryldiamine-containing novolac resin

    WO2018043410A1